Analisis Perbandingan Kinerja Keuangan Bank KBMI 4 di Indonesia: Studi Kasus Menggunakan Pendekatan Common Size dengan Modal Inti Lebih dari Tujuh Puluh Triliun Rupiah - Tobing, Jessi (Jurnal Ilmiah Literasi Indonesia, 2025)
This research aims to analyze the performance of banks in the core capital group of more than seventy trillion rupiah (KBMI 4) in Indonesia. The KBMI 4 banks in Indonesia are BRI, BNI, Bank Mandiri, and BCA. This research is conducted from 2005 to 2024 and focuses on the financial ratios of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return On Assets (ROA), Return On Equity (ROE), and Operating Expenses to Operating Income (BOPO). This research is a quantitative descriptive study using one-way ANOVA test with SPSS application and common size approach. The results show that the CAR ratio of the four banks consistently ranks as very healthy. BCA and Mandiri are more efficient with the highest average CAR. The NIM ratio of the four banks is very healthy, but there is a significant difference in NIM over the past twenty years. BRI has the highest average NIM but tends to decrease. BCA and MANDIRI have the second and third highest NIM, respectively. BRI and BCA consistently have a very healthy ROA ratio, while BNI has the lowest ROA performance. BRI has the highest average ROE ratio, but there is a significant difference over the past twenty years. The BOPO ratio of the banks does not have a significant difference, and BCA is the most efficient in managing operating costs. BNI has the highest BOPO ratio.